Development and Psychometric Evaluation of a Musical Profile Questionnaire (MPQ): A Contribution for Music Education - José Salvador Blasco-Magraner; Gemma Ruiz-Varela; Pablo Marín-Liébana; Gloria Bernabe-Valero (Behavioral Sciences, 2025)
The development of a Spanish musical profile questionnaire, designed to assess both objective aspects of musical engagement and psychological dimensions, represents a significant advancement in the fields of music psychology and music education. Grounded in prior research and created by experts in music education, this instrument offers a comprehensive portrait of musicians by capturing their training, experience, and psychological characteristics. A total of 261 musicians, ranging in age from 16 to 61 years, were recruited through incidental sampling to complete the questionnaire. The final version encompasses both objective indicators of musical dedication and a psychological profile scale. The psychometric evaluation of the scale supported a robust three-factor model comprising “Musical Self-Perception”, “Personal Cost of Music”, and “Existential Contribution of Music”. The 10-item scale demonstrated acceptable internal consistency, along with strong criterion and convergent validity, affirming the instrument’s reliability. The discussion regarding the inclusion or exclusion of items related to theoretical content reflects an evidence-based approach aimed at continuous refinement of the tool. Furthermore, the identification of future directions, including exploration of additional psychological dimensions and potential adaptations for diverse cultural or educational contexts, underscores a forward-looking commitment to the ongoing development and applicability of the questionnaire.